Advances in organisational psychology - Glendon, A. Ian, 1945-; Thompson, Briony M.; Myors, Brett (Australian Academic Press, 2007)
Advances in Organisational Psychology presents an impressive array of contemporary topics in industrial and organisational psychology from the Asia-Pacific region.